Socialization Recording and Bookkeeping Finance Simple for SMEs - Nuniek Fahriani (Kontribusia : Research Dissemination for Community Development, 2023)
The existence of MSMEs cannot be eliminated or avoided from the people of this nation, besides that they are also able to create creativity that is in line with efforts to maintain and develop elements of tradition and culture of the local community. Banter Village has a number of advantages, namely crackers, sills, fish feed, lemongrass, and laos. Person Livelihoods include farmers, construction workers, self-employed (UMKM crackers, sills, fish feed, lemongrass, Laos). As well as professional staff such as teachers, health workers, official employees and others. On average, MSME actors in Banter Village still use the old one manual for their financial calculations, that's why we helped with the complaint faced by MSME actors through social records and financial accounting. This This article aims to analyze the condition of bookkeeping on a micro, small and medium scale creative industry in the joke Village. This Study use A descriptive method with data collection techniques in the form of direct interviews with training. Research result indicates that the company has not carried out financial accounting properly, there is a a mix of personal finance and corporate finance, not familiar with corporate accounting And finance notes And That book is No in the in accordance with That belongs to the entity finance Accounting standards. The results of this effort are difficult to access from formal sources capital because they does not meet the the needs of MSME companies.